AKTIVITAS ANTIDIABETES FRAKSI n-HEKSAN EKSTRAK ETANOL DAUN LENGLENGAN (Leucas lavandulifolia JE. Smith) PADA TIKUS DM TIPE-2 YANG MENGALAMI RESISTENSI INSULIN - Yance Anas; Risha Fillah Fithria; Maulita Cut Nuria; Amprih Martha; Agung Endro Nugroho; Puji Astuti (Kartika : Jurnal Ilmiah Farmasi, 2015)
ABSTRACT This study is an effort to discover new anti-diabetic compounds from natural products in the type-2 diabetes mellitus treatment. The purpose of this study was to determine the potential of n-hexane fraction (FHDL) from lenglengan leaf ethanol extract as an antidiabetic in insulin resistance type-2 diabetic Rat. Insulin resistance was induced by administration of long-acting insulin (Lantus®) 1.80 IU.Kg BW-1.day-1 for 14 days. Insulin resistance rats tested by using parameter fasting blood glucose (FBG), before and after treatment of long-acting insulin. Rat has to type-2 diabetes due to insulin resistance when FBG on day 18 exceeded 85 mg.dL-1. Test results show the animal had insulin resistant.  Rat with the insulin resistance is divided into five treatment groups consisting of one group of diabetic control (treats with CMC-Na 0.5%, 25 mL.Kg BW-1.day-1), three dose groups of FHDL (62.5; 125 and 250) mg.Kg BW-1.day-1 and a positive control group (treats with metformin 150 mg.Kg BW-1.day-1). FHDL and metformin 150 mg.Kg BW-1.day-1 were administered once daily for 14 days. FBG data, before and after treatments were compared. FBG assay is using a reagent kit. The results showed that FHDL (125 and 250) mg.Kg BW-1.day-1 and metformin 150 mg.Kg BW-1.day-1 are shown to have antidiabetic effects in insulin resistance type-2 diabetic rat. FHDL 250 mg.Kg-1.day-1 antidiabetic effect (25.87%) is equivalent to metformin 150 mg.Kg BW-1.day-1 (21.50) (p>0.05). The results of this research can proceed to find the novel antidiabetic compound from the lenglengan leaf ethanol extracts. Key words   : n-Hexane fraction, Lenglengan extract, Anti-diabetic effects, Insulin resistance, Type-2 diabetic rats.